Dirty Hands Make Dirty Leaders?! The Effects of Touching Dirty Objects on Rewarding Unethical Subordinates as a Function of a Leader’s Self-Interest - Cramwinckel, Florien M.; De Cremer, David 1972-; Dijke, Marius van (2013)
We studied the role of social dynamics in moral decision-making and behavior by investigating how physical sensations of dirtiness versus cleanliness influence moral behavior in leader–subordinate relationships, and whether a leader’s self-interest functions as a boundary condition to this effect. A pilot study (N = 78) revealed that when participants imagined rewarding (vs. punishing) unethical behavior of a subordinate, they felt more dirty. Our main experiment (N = 96) showed that directly manipulating dirtiness by allowing leaders to touch a dirty object (fake poop) led to more positive evaluations of, and higher bonuses for, unethical subordinates than touching a clean object (hygienic hand wipe). This effect, however, only emerged when the subordinate’s unethical behavior did not serve the leader’s own interest. Hence, subtle cues such as bodily sensations can shape moral decision-making and behavior in leader–subordinate relationships, but self-interest, as a core characteristic of interdependence, can override the influence of such cues on the leader’s moral behavior.
Keywords: Subordinate; Rewarding behavior; Physical cues; Physical cleansing; Leader; Ethical Leadership